Electrospun P34HB fibres: a scaffold for tissue engineering. (13th August 2014) - Fu, N.; Deng, S.; Fu, Y.; Li, G.; Cun, X.; Hao, L.; Wei, X.; Cai, X.; Peng, Q.; Lin, Y.
Abstract Objectives Amongst the fourth generation of PHAs is bio‐plasticpoly3‐hydroxybutyrate4‐hydroxybutyrate (P34HB); it is thus appropriate to perform novel research on its uses and applications. The main objective of this study was to determine whether electrospun P34HB fibres would accommodate viability, growth and differentiation of mouse adipose‐derived stem cells (mASCs). Materials and methods In the present study, we looked at P34HB in two forms, electrospun P34HB fibres and P34HB film. Morphology of electrospun P34HB fibres and P34HB film were characterized using scanning electron microscopy, fluorescence microscopy and confocal laser scanning microscopy, after cell seeding. Cell adhesion, proliferation and cytotoxicity tests were conducted on both by MTT and CCK‐8 assays, respectively. After being cultured with osteogenic induction, expression of adipogenic genes Runx2, OPN and OCN, were examined by real‐time PCR. Results By scanning electron microscopy, light microscopy and confocal laser scanning microscopy, we observed that the mASCs grew well associated with the P34HB materials. After MTT and CCK‐8 assay, we concluded that P34HB would, indeed, be a material suitable for further cell adhesion and proliferation studies. More importantly, we found that the P34HB matrices promoted expression of Runx2, OPN and OCN with osteogenic induction. Conclusions In this investigation, we can confirm that the electrospun P34HB fibres accommodated survival, proliferation and differentiation of mASCs, and we have been able to draw the conclusion that fibre scaffolds produced by the electrospinning process are promising for application of bone tissue engineering.